St-Etienne Bordeaux St-Etienne. - Galeries des Beaux-Arts, Bordeaux (Bordeaux : Musée des Beaux-Arts Bordeaux, 1987)
Bureau, Cécile ; Celle, Nathalie ; Claude, Annick ; Falsetti, Bianca ; Garrier, Christian ; De Ghellinck, Christophe ; Imbert, Marie-Ange ; Jacob, Hélène ; Odin, Emmanuel ; Outin, Emmanuelle ; Savary, Franck
St-Etienne Bordeaux St-Etienne, Galeries des Beaux-Arts, Bordeaux, du 7 janvier au 18 janvier 1987
boek